National Guard Service Members in Higher Education - Alan M. Parsons; Allison N. Ash (Journal of College Orientation, Transition, and Retention, 2022)
For students in the National Guard (NG), it is reasonable to assume their continual transition in and out of military training may pose academic challenges. With data from qualitative narrative inquiries and using Schlossberg’s transition model as a theoretical framework, this study focused on the transition experiences of seven NG students from two public universities within one south-central state. Findings suggested that NG students experience unique challenges compared to other military-affiliated students, although the difficulties presented do not outweigh their overall academic success. The variability across student experiences suggests opportunities to refine, coordinate, and continue individualized assistance to NG students.